Advancements in electrochemiluminescence-based sensors for ultra-sensitive pesticide residue detection - Irkham; Chico Permana Putra; Clianta Yudin Kharismasari; Salma Nur Zakiyyah; Isnaini Rahmawati; Ivandini Tribidasari Anggraningrum; Wulan Tri Wahyuni; Giovanni Valenti; Francesco Paolucci; Yeni Wahyuni Hartati (Sensing and Bio-Sensing Research)
Pesticides are chemical substances utilized to prevent, control, and eradicate pests or organisms detrimental to crops, playing a pivotal role in minimizing agricultural losses and enhancing yields. However, improper pesticide use can lead to residue accumulation in the surrounding environment, including agricultural products, soil, and water. Detecting pesticide residues in the environment has become imperative. While various techniques such as chromatography, spectrophotometry, optical sensors, and electrochemical biosensors have been reported for pesticide residue detection, they face limitations such as large instrument size and low sensitivity. Currently, electrochemiluminescence (ECL) methods have been developed for pesticide detection. ECL methods can be combined with biosensor techniques or other molecule recognition element to enhance selectivity and specificity. ECL combines controllable electrochemical reaction properties with high photokinetic sensitivity. It can detect analytes with low detection limits (down to pM levels), ensuring rapid measurements and requiring minimal sample volumes for analysis. This literature review discusses the progress in research on detecting pesticide residues using ECL methods. The utilization of ECL, with its unique capabilities, signifies a promising avenue for addressing the shortcomings of traditional detection methods and advancing the field of pesticide residue analysis.